Characterization, subcellular localization and function analysis of myeloid differentiation factor 88 (Pt-MyD88) in swimming crab, Portunus trituberculatus. Issue 95 (December 2019) - Zhou, Su-Ming; Zhao, Jiao-Jiao; Tao, Zhen; Jin, Shan; Wang, Chun-Lin; Zhou, Qi-Cun; Yin, Fei
Abstract: Myeloid differentiation factor 88 (MyD88) is a universal and essential adaptor protein required for the Toll-like receptors (TLRs) pathway activation in invertebrates as well as in vertebrates. Herein, we characterized a MyD88 ( Pt -MyD88) cDNA sequence in the swimming crab ( Portunus trituberculatus ). The Pt -MyD88 ORF is predicted to encode 469 peptides with an N-terminal death domain and a typical C-terminal TIR domain. Real-Time quantitative PCR analysis showed that the Pt -MyD88 transcriptions were constitutively expressed in hemocytes, gill, intestine, heart and muscle in normal crab. The expressions of Pt -MyD88 would be down-regulated by V. alginolyticus or LPS challenge, and be up-regulated by WSSV infection in hemocytes. Intracellular localization showed Pt -MyD88 was distributed mainly in the cytoplasm when it was over-expressed in human cell HEK293T or in Drosophila Schneider 2 (S2). Functionally, over-expression of Pt -MyD88 could either activate the NF-κB in HEK293T cells or activate the promoters of Drosophila antimicrobial peptide genes (AMPs) in S2 cell. In primary cultured hemocytes of swimming crab, after Pt -MyD88 was knocked-down by specific long double strand RNA, the expression of anti-lipopolysaccharide factor1 (ALF1), hyastatin3, crustin1 and crustin3 have been significantly inhibited, while the expression of other AMPs is normal compared to non-specific dsRNA treated cells. Highlights: Full-length cDNAs of Pt -MyD88 was cloned from Portunus trituberculatus. Pt -MyD88 transcriptions were reduced by V. alginolyticus or LPS challenge but induced upon WSSV infection. Over-expressed Pt -MyD88 were distributed mainly in the cytoplasm in HEK293T cell or in S2 cell. Pt -MyD88 could either activate the NF-κB in HEK293 cells or activate the promoters of Drosophila AMPs in S2 cell. In Pt -MyD88 knock-down cells, the expression of ALF1, hyastatin3, crustin1 and crustin3 have been significantly inhibited.